CHEMICAL ANALYSIS OF WATER SOURCED FROM ODO ONA RIVER, IBADAN, SOUTH-WESTERN NIGERIA - FIDELIS NKESHITA; ADEBOLA ADEKUNLE; ADEBAYO ADEDEJI (Journal of Engineering Studies and Research)
The water samples were collected at three different periods of the year from locations around the Oluyole Estate Industrial hub housing many industries and located in Ibadan, South-Western Nigeria. The observed values of the concentration of Aluminium, Chromium, Iron and Sodium show varied concentrations for Sodium (3.01 – 38.02) mg/L, Iron (0.8 – 28.68) mg/L, Chromium (0 – 0.38) mg/L, Arsenic (Not detected) and Aluminium (0 - 0.24) mg/L. The results were compared with standard values of the parameters under consideration as recommended by the World Health Organization (WHO).